Antenatal care at rivers state university teaching hospital, southern Nigeria: who and when? - Nonye-Enyidah, Esther Ijeoma; O. A., Altraide Basil; I. Jumbo, Awopola; Enyidah, Nonyenim Solomon; Terhemen, Kasso (International Journal of Research in Medical Sciences, 2024)
Background: Antenatal care prepares pregnant women physically and psychologically for birth and parenthood. It also prevents, detects and manages health problems affecting mothers and their babies. Objectives were to identify and characterise those attending antenatal care at RSUTH and when they register for antenatal care. Methods: A retrospective study conducted from 1st January, 2015-31st December, 2020 at ANC of RSUTH. Records of 9990 pregnant women who booked for antenatal care were retrieved and reviewed. Socio-demographic characteristics and gestational age at booking were studied. Data was analyzed using SPSS version 23.0. P value <0.05 was statistically significant. Results: During the study period, 9990 pregnant women booked for antenatal care. Most (23.3%) registered in 2016. Mean age at booking was 31.4±4.7 years. Highest age group (62.4%) was 30-39 years. Modal parity was para 0 and majority (37.5%) were para 2-4. Mean gestational age at booking was 20.5±7.5 weeks. More than 70% had tertiary education and 67.9% were traders and civil servants. More than 97% were married and 58.3% registered in their second trimester. When gestational age at booking was compared with the various socio-demographic parameters, those with the differences statistically significant and associated with late booking were educational level, age, parity, occupation and employment status. Conclusions: Most women at booking were in their thirties, second trimester, married, multiparous, working class and had tertiary level of education. Most socio-demographic parameters showed statistically significant differences when compared with the gestational age at booking.